State-of-the-art aortic imaging: part I - fundamentals and perspectives of CT and MRI - Rengier, Fabian; Geisbüsch, Philipp; Vosshenrich, Rolf; Müller-Eschner, Matthias; Karmonik, Christof; Schoenhagen, Paul; Tengg-Kobligk, Hendrik von; Partovi, Sasan (Vasa, 2013)
Over the last two decades, imaging of the aorta has undergone a clinically relevant change. As part of the change non-invasive imaging techniques have replaced invasive intra-arterial digital subtraction angiography as the former imaging gold standard for aortic diseases. Computed tomography (CT) and magnetic resonance imaging (MRI) constitute the backbone of pre- and postoperative aortic imaging because they allow for imaging of the entire aorta and its branches. The first part of this review article describes the imaging principles of CT and MRI with regard to aortic disease, shows how both technologies can be applied in every day clinical practice, offering exciting perspectives. Recent CT scanner generations deliver excellent image quality with a high spatial and temporal resolution. Technical developments have resulted in CT scan performed within a few seconds for the entire aorta. Therefore, CT angiography (CTA) is the imaging technology of choice for evaluating acute aortic syndromes, for diagnosis of most aortic pathologies, preoperative planning and postoperative follow-up after endovascular aortic repair. However, radiation dose and the risk of contrast induced nephropathy are major downsides of CTA. Optimisation of scan protocols and contrast media administration can help to reduce the required radiation dose and contrast media. MR angiography (MRA) is an excellent alternative to CTA for both diagnosis of aortic pathologies and postoperative follow-up. The lack of radiation is particularly beneficial for younger patients. A potential side effect of gadolinium contrast agents is nephrogenic systemic fibrosis (NSF). In patients with high risk of NSF unenhanced MRA can be performed with both ECG- and breath-gating techniques. Additionally, MRI provides the possibility to visualise and measure both dynamic and flow information.
Gesehen am 22.12.2021